Towards An Improvement of Hospital Services and Streamlining of Health Care Costs: The DRG Analysis in Italy - MC Gioviale; FM Accardo; A Geraci; F Damiani; P Damiani; G Tomasello; M Bellavia; AI Lo Monte (Tehran University of Medical Sciences, 2012)
The term Diagnosis-related Group (DRG) refers to a classification system used to assess hospital services with the aim of a better management of health care costs and improving performance. The DRG system focuses on the utilization of resources, and is not concerned with the specific type of care provided to the patient. This system highlights any diseconomies and eventual critical aspects of the hospital system. This article, starting from the history of heath care financing in Italy and pointing out the difficulty to define the "quality" of health care services, describes the variables used to evaluate correctly hospital performance based on the DRG system. These include Average Length of Stay, Average Daily Patient Load, Comparative Performance Index, and Case Mix Index.